2012
DOI: 10.1186/1471-244x-12-143
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns in major depressive disorder after an inadequate response to first-line antidepressant treatment

Abstract: BackgroundThe aim of the study was to determine the most common pharmacological strategies used in the management of major depressive disorder (MDD) after an inadequate response to first-line antidepressant treatment in clinical practice.MethodsMulticenter, non-interventional study in adult outpatients with a DSM-IV-TR diagnosis of MDD and inadequate response to first-line antidepressant medication. Multiple logistic regression analyses were performed to identify independent factors associated with the adoptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…This is similar to the 20% quoted in a study done in Korea [20]. In a multi-centre study in Spain, Garcia-Toro et al found that about 19% patients [29] were prescribed augmentation therapy, with atypical antipsychotics being the more common choice (rather similar to our case).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is similar to the 20% quoted in a study done in Korea [20]. In a multi-centre study in Spain, Garcia-Toro et al found that about 19% patients [29] were prescribed augmentation therapy, with atypical antipsychotics being the more common choice (rather similar to our case).…”
Section: Discussionsupporting
confidence: 90%
“…For example, researchers in France, based on a general practice database, showed that 16% of patients switched antidepressants, with 72% occurring within 3 months of treatment initiation [28]. Others reported switching for the purpose of optimizing treatment in about 40% of patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…The low application of the combination strategy in this primary-care population may reflect the NICE recommendations in effect during the study period, which state that this approach should only be implemented following discussion with a consultant psychiatrist 26,30 . Few studies have reported on treatment choices after first-line therapy in clinical practice and none have investigated choices made in primary care [41][42][43] . A small study in Spain of psychiatrists' choices of second-line treatment in community care noted that switching was the most common strategy (40%), while combination and augmentation were implemented to a lower degree (24% and 18%, respectively) 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported on treatment choices after first-line therapy in clinical practice and none have investigated choices made in primary care [41][42][43] . A small study in Spain of psychiatrists' choices of second-line treatment in community care noted that switching was the most common strategy (40%), while combination and augmentation were implemented to a lower degree (24% and 18%, respectively) 41 . Surveys of psychiatrists have also reported that their preferred option would be switching 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…The current gold-standard treatment for psychiatric illnesses, MDD and anxiety disorders in particular, are antidepressants medications. Though antidepressants have a relatively high efficacy, a large proportion of individuals with psychiatric illnesses do not respond to these first-line treatments, and thus need to try alternatives (Garcia-Toro et al, 2012). Further, many antidepressant users also experience side effects such as restlessness, nausea, vomiting, anxiety, insomnia, sexual dysfunction, gastrointestinal cramps and diarrhea, and headaches that can make the arduous process of searching for effective treatments even harder (Stahl, 1998).…”
Section: Treatment Feasibilitymentioning
confidence: 99%